(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The majority of cities have subsurface drainage systems, and it is the responsibility of municipal corporations to keep cities clean, healthy, and safe. If the drainage system is not properly maintained, clean water can become contaminated by drainage water, which increases the risk of the spread of infectious diseases. Since dangerous gases are odourless if exposed for a long period of time, they can cause major health issues, yet individuals who clean drains are unaware of the risk of a sudden attack of deadly gas. During the past few decades, a lot of dangerous mishaps happened as a result of improper gas leakage detecting systems being used. An efficient monitoring system is required in the drainage channels to solve all of these issues. The suggested detection system includes two gas sensors for methane, hydrogen sulphide, and carbon monoxide. Since carbon monoxide, hydrogen sulphide, and methane gases are extremely harmful to humans, the suggested system will notify users by an LED glow once each gas sensor’s threshold is reached.